PERAN ICE BREAKING DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA - Mohammad Fajar Shodiq (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to examine and analyze the role of ice breaking in improving student concentration based on previous research results. Declining student concentration is one of the problems often encountered in the classroom learning process. This condition can be caused by monotonous learning, long learning durations, and a lack of variety in learning strategies that take into account the psychological conditions of students. One strategy that can be used to overcome this problem is the application of ice breaking in learning. The method used in this study is a literature review by examining various national and international scientific journal articles, reference books, and other academic publications relevant to the research topic. The data obtained was analyzed using content analysis techniques to identify key findings related to the implementation of ice breaking in learning. The results of the study show that ice breaking plays a positive role in improving students' concentration by creating a pleasant learning atmosphere, reducing boredom, and helping to restore students' focus on learning. Thus, the application of ice breaking can be used as an effective learning strategy to support the achievement of learning objectives.